Los suelos en la enseñanza de la teoría ácido-base de Lewis. Una estrategia didáctica de aprendizaje por investigación - Salcedo Torres, L. E.; García García, José Joaquín (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1997)
This article describes and analyses the results obtained in a didactical experimental strategy, structured in the Teaching and Learning model which is based on research. The students are involved in situations, where problems related with the soil are used in order to help the significative construction of the acid and base’s concepts related to the Lewis’ Theory in order to increase the students mental ability for analysing and synthesizing and also to develop their attitudes towards science.